Good Citizen Values in Rasuna Said’s Struggle as a Character-Based History Learning Source - Finna Wijayanti; Wildhan Ichzha Maulana; Miftahuddin Miftahuddin (STAI Hubbulwathan Duri, 2024)
This research aims to describe Rasuna Said’s good citizen value based on an androgynous historical perspective and its relevance to the contextualization of character-based history learning in the “Merdeka Curriculum”. This research is included in the qualitative based on a literature review and uses a content analysis approach. Primary sources in this research, Fikiran Ra'jat magazine, Menara Poetri newspaper, and supported by several other secondary sources, all provide a contextualization of Rasuna Said’s civic knowledge, civic skills, and civic disposition in the history of her struggle. The results of this study are as follows: (1) to explain Rasuna Said’s struggle based on an androgynous historical perspective; (2) Describe Rasuna Said’s good citizen values, in this case, civic knowledge is shown through her critical attitude towards the problem of gender inequality and her decision to establish several formal educational institutions for the empowerment of women; civic skills are shown from the complexity of her skills, interaction style, and participation in society regardless of differences in individual and group backgrounds; then civic disposition is shown from her appreciation of the values and principles of gender equality for women which is actualized through her contribution to the organizations “Sarekat Ra’jat” and “PERMI”. (3) The value of good citizen Rasuna Said can strengthen the competence of the Pancasila student profile through its integration in the history learning of class XI Phase F of the “Merdeka Curriculum” material history of the nation’s struggle. The introduction of Rasuna Said’s good citizen values through history learning can be a solution to help students become democratic, superior, and productive citizens in the 21st century.